Penerapan Sistem Informasi Inventory Gudang Berbasis Web pada PT Laz Coal Mandiri - Dwi Ratna Sari; Arif Supriyanto (Universitas Katolik Widya Karya Malang, 2023)
There are jobs in the warehouse that are still not optimal, one of which is managing administration and other activities related to warehouse mechanics and inventory. In the warehouse management section, employees record incoming goods, outgoing goods, and stock of goods by recording them in the inventory book, resulting in a buildup of inventory which often causes discrepancies between the release of goods and transaction funds. The research method used to solve problems is by using interviews and observation methods and for system development using the object oriented method. The results of this research produce a warehouse inventory information system that is capable of carrying out web-based warehouse recording transactions, so it is hoped that it can help with problems in PT Laz Coal's warehouse inventory.